Severity and Risk Rating of Drug-Drug Interaction Potency in Chronic Kidney Disease in Public Health Hospital - Okta Muthia Sari; Aditya Maulana Perdana Putra (Research Center for Rational Use of Drugs (RCRUD), 2024)
Background: Chronic kidney disease has emerged as a prominent cause of mortality worldwide in the last two decades. Drug interactions are a significant problem in individuals with chronic kidney disease, as they often receive numerous concurrent treatments. The aim is to examine the frequency of drug-drug interactions in outpatient treatment for chronic renal disease, classified according to their severity and risk level. Furthermore, the study aims to demonstrate the combined effect of the most common drug-drug interactions potency and associated risk factors. Methods: This study is a retrospective cross-sectional analysis of outpatients diagnosed with chronic kidney disease at Ansari Saleh Public Hospital in Banjarmasin, Indonesia. Medical records from 2022 were obtained retrospectively from computerised sources. The evaluation of potential interactions between drugs was conducted using Lexicomp®. The categorical data were displayed as percentages, and the continuous variables were depicted as means. Results: The study found that most drug interactions fell into the moderate severity (77.1%) and category C (75.5%) for the risk assessment. The prevalence of drug-drug interactions was 83.6% and the average number of potential drug interactions per patient was 3.34 ± 3.481. The concurrent use of candesartan and furosemide was the most prevalent drug-drug interaction (5.1%). The number of prescribed medications was a notable determinant for probable drug-drug interactions (p < 0.05). Conclusion: Identifying and averting potential drug-drug interactions is crucial to guarantee patient safety.